Lathyrus ibicuiensis (Fabaceae, Faboideae), a new species endemic to Southern Brazil - Aragão De Oliveira, Maria De Lourdes Abruzzi; Miotto, Silvia T.s.; Iganci, João R.v. (Phytotaxa, 2015)
A new species of Lathyrus is described. This species occurs in rocky fields, in a restricted protected area from Southern Brazil. Lathyrus ibicuiensis resembles L. linearifolius in having simple tendrils, but differs in ovate to lanceolate stipules, by ramified branches, and by elliptic, oblong to rarely obovate leaflets, as well as in its geographic distribution. A description and illustration are provided together with a key for identification of similar species occurring in Southern Brazil.